GetijdenBoek = Book of tides - Wauman, Wim, 1976- (Antwerpen : Pascal De Groote, 2019)
Kunstenaar Wim Wauman draagt dit boek op aan zijn zoon Isaac Wauman. Een samenraapsel van teksten en illustratie over de meest uiteenlopende onderwerpen, teksten en illustraties, en allemaal hebben deze thema's een band met kunst.
In this publication, multidisciplinary artist Wim Wauman presents the results of his artistic doctoral research on the tension between art and (traditional) craftsmanship ?Making Waves: A Play with Arts and Crafts.? The author sought (and found?) A learning path ( skill in applications with wood veneer), in collaborations, brainwashing, and in increased (personal) engagement which ultimately led to the experimental ?Blauwhaus? complex. At first sight an installation / exhibition designed to work with a ?dream team? of guest artists, but also a purifying ?twilight zone? that was created to create a creative ?flow? and stimulate the imagination.00Wauman compiled the (Blauwhaus) GetijdenBook Book of Tides, in which a selection of his own recent artworks and projects is documented, supplemented with new Dutch or English texts (including hermetic pieces of prose, free verses and letters), a whimsical ?FenceCrossPhilosophy ?, an encyclopedic? Wikileaks? section and ?A Play with Arts and Crafts?. The book also contains a Dutch poem by Leen Huet and illustrated reports on the interventions of dream team employees such as Alice McCabe, Hadewych Becuwe & Kelly Schacht, Hilde Borgermans, Ilse Van Roy, Isabel Bouttens, Maria Degrève, Pieter Léon Vermeersch, Robbert & Frank Frank & Robbert, Veerle Verschooren and Warre Mulder.
Includes bibliographical references.
Text in Dutch and English.
Keywords: Art and craft debate; Art and craft debate; Art -- Philosophie; Art -- Philosophy; Art -- Philosophy; Artisanat dans l'art.; Débats sur l'art et l'artisanat.; Handicraft in art; Handicraft in art